Prevalence and Factors Associated with Mental Health Disorders Among Nurses in Acute Care Settings in Riyadh: A Cross-Sectional Study - AlGhamdi, Khalid S; Lalithabai, Diana S; Owaishiz, Buhaiseh (Universitas Airlangga, 2025)
Introduction: Nurses working in acute healthcare settings often experience mental health disorders while caring for palliative care and critically ill patients. As the backbone of the healthcare system, their mental well-being warrants greater attention. This study aims to assess the prevalence of mental health disorders and associated factors among nurses working in selected acute care settings in Riyadh, Saudi Arabia Method: This cross-sectional study examined the mental health of nurses employed in acute healthcare settings in Riyadh, Saudi Arabia. A total of 485 participants were recruited using simple random sampling and proportionate allocation methods. Data were collected using an online questionnaire based on the Depression, Anxiety, and Stress Scale - 21 Items. Data were analyzed using descriptive statistics and inferential tests, including t-tests and a one-way analysis of variance, to determine associations between mental health outcomes and participant characteristics. Results: The findings indicate that 59.8% of nurses reported normal depression levels, 28.2% experienced mild to moderate depression, and 12% suffered from severe or very severe depression. Regarding anxiety, 51.5% reported normal levels, 24.1% experienced mild to moderate anxiety, and 24.3% reported severe or extreme anxiety. Concerning stress, 73.4% of respondents indicated normal stress levels, 18.1% experienced mild to moderate stress, and 8.5% reported severe or extremely severe stress. Younger nurses and those with lower work experience exhibited significantly higher levels of stress, anxiety, and depression compared to their more experienced counterparts. Conclusions: The study findings suggest that while most respondents experienced average levels of stress, anxiety, and depression, more than one-fourth of nurses reported severe to very severe levels of anxiety and depression, with 12% experiencing severe or very severe depression. These results highlight the urgent need for targeted mental health interventions, improved workplace policies, and supportive environments for nurses working in acute healthcare settings, which may enhance their mental well-being, job satisfaction, and quality of patient care.